2022
DOI: 10.1007/s40618-022-01755-0
|View full text |Cite
|
Sign up to set email alerts
|

Risk of non-alcoholic fatty liver disease in patients with chronic plaque psoriasis: an updated systematic review and meta-analysis of observational studies

Abstract: Purpose Chronic plaque psoriasis is associated with the presence of non-alcoholic fatty liver disease (NAFLD), but the magnitude of this association remains currently uncertain. We aimed to investigate the magnitude of the association between psoriasis and the risk of prevalent and incident NAFLD, and to assess whether psoriasis severity and/or psoriatic arthritis are associated with a greater risk of NAFLD. Methods A systematic review and meta-analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 40 publications
(49 reference statements)
3
46
2
Order By: Relevance
“…In addition, individuals with psoriasis often have high alcohol consumption which also impacts liver function ( 35 ). Patients with psoriasis have higher risk of NAFLD ( 6 , 7 ), however, studies on risk of psoriasis in individuals with NAFLD are scarce. Importantly, circulating pro-inflammatory cytokines associated with both psoriasis and NAFLD drive a chronic low-grade inflammation that could lead to progression of liver damage and worsening of the psoriatic skin ( 11 , 12 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, individuals with psoriasis often have high alcohol consumption which also impacts liver function ( 35 ). Patients with psoriasis have higher risk of NAFLD ( 6 , 7 ), however, studies on risk of psoriasis in individuals with NAFLD are scarce. Importantly, circulating pro-inflammatory cytokines associated with both psoriasis and NAFLD drive a chronic low-grade inflammation that could lead to progression of liver damage and worsening of the psoriatic skin ( 11 , 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…The last decades several observational studies have investigated the association between psoriasis and NAFLD ( 6 , 7 ). In the present study, we find a higher risk of psoriasis in individuals with NAFLD and increased liver fat content, however, confounding and reverse causation are inherent limitation in observational studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a significantly increased risk of in-hospital mortality related to alcohol in psoriasis patients with an SMR of 4.46 for men and 5.6 for women [ 4 ]. A recent systematic review and meta-analysis identified 15 studies with 249,933 psoriasis patients with an OR of 1.96 for NAFLD compared with 1,491,402 healthy controls [ 43 ]. This risk was higher in patients with severe psoriasis and psoriatic arthritis potentially due to a greater systemic inflammatory burden and altered metabolic parameters with increasing insulin resistance and obesity.…”
Section: Alcohol Is Implicated In the Comorbidities Associated With P...mentioning
confidence: 99%
“…They are predisposed to liver fibrosis for a variety of reasons, one of which is non-alcoholic fatty liver disease (NAFLD), a prevalent liver disease affecting approximately 25% of the general population (3). NAFLD has been found to be strongly associated with psoriasis in previous meta-analyses (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%